A unified approach to the revelation of public goods preferences and to optimal income taxation - Felix Bierbrauer (Max Planck Institute for Research on Collective Goods, 2008)
We study a large economy model in which individuals have private information about their productive abilities and their preferences for public goods. A mechanism design approach is used to characterize implementable tax and expenditure policies. A robustness requirement in the sense of Bergemann and Morris (2005) yields individual incentive compatibility constraints that are equivalent to those in the theory of optimal income taxation in the tradition of Mirrlees (1971). Adding a requirement of coalition-proofness yields a set of collective incentive conditions which are akin those in the literature on public goods provision under private information on preferences, in the tradition of Clarke (1971) and Groves (1973).
Keywords: D71; D82; H21; H41; 330; Optimal Taxation; Public goods provision; Revelation of Preferences; Robust Mechanism Design; Optimale Besteuerung; Öffentliches Gut; Offenbarte Präferenzen; Mechanism; Theorie